Flood risk mapping in Kota Tinggi, Malaysia - Ibrahim, Ab. Latif (2012)
According to the Department of Irrigation and Drainage in Malaysia, about 29, 000 sq. km, or 9% of the total land area and more than 4.82 million people (i.e. 22% of the population) are affected by flooding annually. Damage caused by flooding is estimated about RM 915 million (£160 million). An unprecedented heavy rainfall occurred in Malaysia in December 2006 to January 2007. The consequence of this extreme event has resulted severe impact on few area of Malaysia where Kota Tinggi in Johor state is one the affected area. The objectives of this study are 1) to study the capability of SOBEK for flood simulation, 2) to study the impact of different flood scenarios on those elements in inundated area. Different types of flood maps have been developed where each flood maps is conveyed its spatial information to the end-users. Of these flood maps, flood risk map is very essential as it includes information on the consequences of flooding. Risk results from the interaction of hazard and vulnerability.